Microbiological indicator of medium filth (najs mutawassitah) in ready to eat food : towards standardization of toyyibah food - Ainin Azwani binti Abdul Rafa (Kulliyyah of Allied Health Sciences , International Islamic University Malaysia, 2015)
This study was conducted to evaluate the severity of medium filth contamination in ready to eat food (RTE) as to confirm the definition of halal food that supposedly not contaminated with najs mutawassitah. A total of 52 human stools samples were collected from voluntary healthy subjects according to method as explained by Chessbrough (1987) and the screening of bacteria in the human stools samples were done according to traditional microbiological analysis methods. Determinations of bacterial growth curves were performed using NanoDrop 1000 UV-VIS Spectrophotometer at 630nm where the initial and end of lag times for each of bacteria was determined. The growth evaluation of faecal borne bacteria in RTE food was performed using prepared fried rice samples. The prevalent study of food-borne/faecalborne bacteria was performed in 120 RTE fried rice collected from four different types of food premises in the town of Kuantan, Pahang. The results showed that healthy human stools which fall under najs mutawassitah contained high amounts of presumptive pathogenic bacteria specifically E. coli, S. aureus, B. cereus, Aromonas spp. and Salmonella spp. at different mean values. Total plate count (TPC), coliform and F. coliform were used as indicators in detecting the presence of pathogenic bacteria in human stools as well as for contamination of najs mutawassitah. Average lag phase time for faecal borne bacteria was around 60 minutes. Thus consumption of food within one hour should not give any significant health effects. Consuming food which contains faecal borne bacteria within one to two hours would give either low risk health effect or none at all. Consuming food after two hours has medium risk. Consuming food after three or four hours has the highest health risk. If the contamination of human stools in the food is in small quantity (1-2 drops), it may have no health risk at all. The small amount of bacteria in food may need more time to adapt with the new environment. If the human stools are in higher volume (more than 2 drops or about 1 ml) then it will start to contaminate the food and could then lead to health risks. If RTE food were contaminated with small amount (about 0.1 ml) of human stools and were left over at ambient temperature (about 37oC) for a certain period of time (about 4 hours), it would start to have bacteria contamination and may cause health risks. If the level of health risk was translated according to Shariah law, RTE foods which were contaminated with higher amount (more than 2 drops) of human stools or contaminated with small amount (1-2 drops) of human stools and were left exposed at ambient temperature for more than 4 hours can be considered as shubhah/makhrooh to be eaten. The study also indicated that RTE fried rice sold at markets have medium to high health risks. Fresh or just cooked fried rice which are sold at night markets have less health risks compared to those that are sold at other type of food premises.